Conocimiento y práctica de higiene de manos según momentos en enfermeros del Hospital Regional de Loreto Iquitos 2023 - Saldaña Montalvo, Lady Stefany (2024)
The objective was to determine the relationship that exists between knowledge and practice of clinical hand hygiene according to moments, in nurses at the Regional Hospital of Loreto Iquitos 2023. The method was quantitative, descriptive, correlational, cross-sectional design. The population and sample were made up of all 82 nurses from the Medicine, Surgery, Gynecology, Pediatrics and Maternity care services of the Loreto Regional Hospital. The technique used was the survey and observation, while the instruments were the Clinical Hand Hygiene Knowledge Questionnaire according to moments and the Clinical Hand Hygiene Practice Checklist according to moments. The SPSS version 24.0 program was used for data processing, descriptive statistics were used for the univariate analysis, and chi square (X2) was used for the inferential statistical bivariate analysis. The results were: at the level of clinical hand hygiene knowledge according to moments, 58.5% had high knowledge, 25.5% had medium knowledge and 15.9% had low knowledge; Regarding clinical hand hygiene practice according to moments, 36.6% had partial practice, 35.4% had insufficient practice and 28.0% had good practice. Concluding that, there is an association between both variables with a significance value of 0.000 (p<0.01) Kendall's Tau-b.